PENGARUH METODE FUN LEARNING TERHADAP MINAT BELAJAR BAHASA ARAB - Nasrullah, M. Alaika; Muhajiroh , Ninik (JIP: Jurnal Ilmu Pendidikan, 2024)
This research aims to determine the effect of the fun learning method on students' interest in learning Arabic at Madrasah Ibtidaiyah Muawanah 1 Barurejo, Banyuwangi Regency, East Java, Indonesia. The data collection methods used in this research are questionnaires, observation, documentation. Meanwhile, to test the validity of the data, use the Pearson Correlation formula to find the reliability of the data using the Cornbach Alpha formula. Then for hypothesis testing using the F test and T test, to test normality using the formula Kolmogrov-Smirnov. Data analysis uses linear regression analysis simple. The results of this research show that from these data, if interpreted using the test criteria, namely the results of the t test > t table, meaning 1.186> 0.682, then Ha is accepted, so the results of this research show that the fun learning method is classified as good. And if interpreted using the testing criteria, namely the results of the t test > t table, meaning 3.537 > 0.682, then Ha is accepted, so the results of this study show that interest in learning Arabic is classified as good. Then from the results linear regression test, it was found that the fun learning method (X) had a very weak influence on students' interest in learning Arabic (Y) at 4.1%, the remaining 95.9% was influenced by other variables.